Application of the Deliberation Method for the Study of the Book of Fiqh In Improving Santri's Critical Thinking Ability - Sri Ayu Utami; Suteja; Mahbub Nuryadien; Iis Arifudin (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
Based on the United Nations Educational, Scientific and Cultural Organization (UNESCO) survey in 2022, Indonesia's education quality is ranked bottom 10 out of 14 countries. This shows that the low level of critical thinking skills is caused by an ineffective learning process. So a method is needed, namely an effective deliberation method in the learning process. This study aims: (1) to find out how the application of the deliberation method used by students, (2) to find out how the level of critical thinking of students, (3) to find out the effectiveness of the deliberation method in improving the critical thinking skills of students of Pondok Darussalam Buntet Pesantren Cirebon. This study used quantitative descriptive research with a correlational research approach. Data collection techniques in this study used observation, questionnaires, interviews and documentation. In addition, the analytical techniques used are validity tests, reliability tests, normality tests, homogeneity tests, hypothesis tests, product moment correlations, coefficients of determination, and significance tests (t tests). The results of this study are: (1) Application of the deliberation method of fiqh book study at the Darussalam Buntet Islamic boarding school in the very good category with a value of 87.28% which is in the interval of 80% - 100%,  (2) Improvement of critical thinking skills of students of the Darussalam Buntet Islamic boarding school in Cirebon is included in the very good category with a value of 82.24% which is in the interval of 80% - 100%, (3) The effect of applying the deliberation method of fiqh book study on the critical thinking ability of students of the Darussalam Buntet Islamic boarding school in Cirebon shows a positive correlation of 0.713 which shows a high correlation because it is in the interval 0.60 – 0.799. Then the value of the coefficient of determination is 50.83%, the remaining 49.17 is influenced by other factors. This shows that the influence of the application of the deliberation method of fiqh book study on the critical thinking ability of Pondok Darussalam Buntet Pesantren Cirebon students is significant or effective.